Temporal and Distance Effects on Land Values – Examples from the Meck lenburg Lake County in Germany - Fuchs, Clemens; Limpächer, Sarah Katharina; Fock, Theodor; Kasten, Joachim; Ehrhardt, Agnes (New Countryside, 2024)
In the past decade the land market in Eastern Germany was characterized by a relatively high level of land mobility and severe land price hikes. Land prices in individual regions differ considerably, however. This paper has examined whether obtaining a higher sales price for a utilised agricultural area in particular bounds has a spillover effect on neighbouring bounds so that higher prices can be secured there, too. The region selected for this study was the Mecklenburg Lakeland administrative district, the largest administrative district in Germany. The local team of land value appraiser provided a feature based description of all individual land sales for the period from 2001 to 2016 covering a total of 12,045 anonymised records; this did not include cases of acquisitions of whole enterprises and/or share deals however. From these data, ultimately 3,046 sales of arable land have been analysed by means of geographic information systems and panel regression analysis. It was examined whether the achievement of higher prices in a certain district radiates to neighboring districts, so that higher prices are also achieved there. It can be concluded that information is exchanged between market participants, although many perceive the land market as relatively non-transparent. Distance decay effects on land values were found, which means that high land values of one spot radiate at least to neighboring districts up to a distance of 30 km. The analysis underlines therefore that spatial effects have influence on agricultural land markets. “Hot spots” in one area influence neighboring areas. Local hot spots arise through the derived demand of biogas plants, theactivities of investors or the local competition conditions.